2010
DOI: 10.1039/c005272h
|View full text |Cite
|
Sign up to set email alerts
|

Residues 762–801 of PLD1 mediate the interaction with PED/PEA15

Abstract: The interaction of Phospholipase D1 (PLD1) by its C-terminal domain D4 with PED/PEA15 has been indicated as a target for type 2 diabetes. PED/PEA15 is overexpressed in several tissues of individuals affected by type 2 diabetes and its overexpression in intact cells and in transgenic animal models impairs insulin regulation of glucose transport by a mechanism mediated by the interaction with D4 and the consequent increase of protein kinase C-alpha activity. Expression of D4 or administration of a peptide mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…This K D is in very good agreement with that previously reported (22) and supports the view that the binding of PLD1 to PED/PEA15 is essentially mediated by the region D4 α‐spanning residues 712–818.…”
Section: Resultssupporting
confidence: 92%
“…This K D is in very good agreement with that previously reported (22) and supports the view that the binding of PLD1 to PED/PEA15 is essentially mediated by the region D4 α‐spanning residues 712–818.…”
Section: Resultssupporting
confidence: 92%
“…These findings in addition to our finding that PLD1 co-localizes with PEA-15 in iBMK cells raised the question if binding of the two proteins is necessary for the observed enhancement of ERK activity in H-Ras expressing iBMK cells. The PEA-15 binding region of PLD1 has already been mapped to a C-terminal domain D4 (AA 712-1074) and the residues 762-801 within this domain have been identified as the shortest PEA-15 binding segment (Figure 7A) (Doti et al 2010, Zhang et al 2000). Here we used a PLD1 construct only consisting of the D4 domain (Figure 7B) and lacking catalytic activity (PLD1-D4).…”
Section: Resultsmentioning
confidence: 99%
“…Together with the positive effect of D4 expression on glucose-induced insulin secretion, this may contribute to the amelioration of whole body glucose homeostasis. Recently, Doti N. et al have shown that the use of a restricted D4 domain, named D4alpha, or the use of short PLD1 peptides that could mimic PED/PEA-15 binding interface can be used as antagonists to prevent the association of PLD1 from PED/PEA-15 [24]. This study provided thus new short, selective and efficient PED/PEA-15-PLD1 antagonists alternative to the D4 that could be transduced to the cells and tissues by adenoviral gene delivery approach.…”
Section: Discussionmentioning
confidence: 99%